PENGATURAN POLA HIDUP DAN AKTIVITAS FISIK MENINGKATKAN UMUR HARAPAN HIDUP - Alex Pangkahila (Sport and Fitness Journal, 2013)
Human life expectancy is very dependent on the process of aging, and the aging process is not nature but is caused by several factors including: excessive activity (Wear and Tear Theory), hormonal (Neuroendocrinology Theory), genetic (The Genetic Control Theory), and free radicals (The Free Radical Theory). Understanding of the nature that is not appropriate is believed by many community groups and even linked to problems that impede true religion in society. A true old age group the number is gradually increasing and this means increasing life expectancy. Actually, life expectancy can be scientifically programmed with faith. The development of science and technology so advanced in many fields, including health sciences and many other disciplines that support positive impact for the control of the aging process that increases a person's life expectancy. Pattern of life is very important role determining the aging process. This is evidenced by the report that 64% of deaths are caused by unhealthy lifestyles. Setting lifestyle that includes sleeping patterns, eating, working, break, and recreation, especially in determining the age of a person. Excess work or excess physical activity and lack of sleep will shorten the lifespan because penuaannya process occurs faster than their healthy life. This situation will reduce levels of some hormones and increases free radicals which will accelerate the aging process. Based on various research reports that turns the aging process can be slowed by setting lifestyle that consists of several elements of the lifestyle patterns such as sleep, work, eat, exercise and recreation. It is recommended that all people a healthy lifestyle as early as possible since the kids up for life.